Candida albicans chronic colonisation in cystic fibrosis may be associated with inhaled antibiotics. Issue 7 (9th June 2015) - Noni, Maria; Katelari, Anna; Kaditis, Athanasios; Theochari, Ioanna; Lympari, Ioulia; Alexandrou‐Athanassoulis, Helen; Doudounakis, Stavros‐Eleftherios; Dimopoulos, George
Summary Candida albicans is increasingly recognised as a coloniser of the respiratory tract in cystic fibrosis (CF) patients. Yet, the potential role, if any, of the micro‐organism in the progress of the disease remains unclear. In this study, we investigated the association between inhaled antibiotics and C. albicans chronic colonisation in patients with CF. A cohort of 121 CF patients born from 1988 to 1996 was, respectively, studied. The medical records of each patient were reviewed from the first time they attended the CF Centre until the occurrence of C. albicans chronic colonisation or their last visit for the year 2010. Chronic colonisation was defined as the presence of C. albicans in more than 50% of cultures in a given year. A number of possible confounders were included in the multivariate logistic regression analysis to identify an independent association between inhaled antibiotics and C. albicans chronic colonisation. Fifty‐four (44.6%) of the 121 patients enrolled in the study developed chronic colonisation by the micro‐organism. Multivariate logistic regression analysis determined the independent effect of inhaled antibiotic treatment on the odds of chronic colonisation (OR 1.112, 95% CI [1.007–1.229], P = 0.036). Candida albicans chronic colonisation may be associated with the duration of inhaled antibiotic treatment.